Impact of ICT on Human Resource Management Practices (A Review of Literature) - Nanda, M; Mahalik, DK (International Journal of Computer Sciences and Engineering, 2025)
The objective of this study is to review some papers in the field of impact of Information and communication technology (ICT) in Human Resource Management (HRM) practices. Information and Communication Technology (ICT) is the process of sharing information by using all kinds of electronics devices like computers, telephones etc. ICT is an important tool for decision making and managing different managerial functions in the organizations. Information technologies have changed the entire process of operating a business process. Over the last decade ICT have been adopted by the HR department in different HR functions like recruitment, selection, training, performance management, and compensation functions as it contributes to the development and profitability of the organization by reducing costs, facilitating information flow and thereby helping the HR managers to take effective decisions and gain a competitive advantage. In the past few years ICT has been acting as an effective tool for organizational performance. The objective of ICT is to support creation, transfer and application of information related to human resources or employees in organizations. Thus, effective development and implementation of ICT (HRIS) requires a foundation in several rich literatures. This paper presents the functions, applications and various concepts of ICT (HRIS) with a focus on its potential role in an organization